On (k_1A_1, k_2A_2, k_3A_3)-edge colourings in graphs and generalized Jacobsthal numbers - Piejko, Krzysztof; Trojnar-Spelina, Lucyna (Annales Mathematicae Silesianae, 2025)
In this paper we introduce a new kind of generalized Jacobsthal numbers in a distance sense. We give the identities and matrix representations for them and their connections with the Fibonacci and the Pell numbers. We also describe the interpretations of these numbers in terms of some kind of (k1A1, k2A2, k3A3)-edge colouring and quasi colouring.